Lone-Pair-Induced Structural Ordering in the Mixed-Valent 0D Metal-Halides Rb(23)Bi(III)(x)Sb(III)(7–x)Sb(V)(2)Cl(54) (0 ≤ x ≤ 7) - Benin, Bogdan M. (Chem Mater, 2021)
[Image: see text] Mixed-valent metal-halides containing ns(2) lone pairs may exhibit intense visible absorption, while zero-dimensional (0D) ns(2)-based metal-chlorides are generally colorless but have demonstrated promising optoelectronic properties suitable for thermometry and radiation detection. Here, we report solvothermally synthesized mixed-valent 0D metal-halides Rb(23)Bi(III)(x)Sb(III)(7–x)Sb(V)(2)Cl(54) (0 ≤ x ≤ 7). Rb(23)Sb(III)(7)Sb(V)(2)Cl(54) crystallizes in an orthorhombic space group (Cmcm) with a unique, layered 0D structure driven by the arrangement of the 5s(2) lone pairs of the Sb(III)Cl(6) octahedra. This red material is likely the true structure of a previously reported monoclinic “Rb(2.67)SbCl(6)” phase, the structure of which was not determined. Partially or fully substituting Sb(III) with isoelectronic Bi(III) yields the series Rb(23)Bi(III)(x)Sb(III)(7–x)Sb(V)(2)Cl(54) (0 < x ≤ 7), which exhibits a similar layered 0D structure but with additional disorder that yields a trigonal crystal system with an enantiomorphic space group (R32). Second harmonic generation of 532 nm light from a 1064 nm laser using Rb(23)Bi(III)(7)Sb(V)(2)Cl(54) powder confirms the noncentrosymmetry of this space group. As with the prototypical mixed-valent pnictogen halides, the visible absorption bands of the Rb(23)Bi(III)(x)Sb(III)(7–x)Sb(V)(2)Cl(54) family are the result of intervalent Sb(III)–Sb(V) and mixed-valent Bi(III)–Sb(V) charge transfer bands (CTB), with a blueshift of the absorption edge as Bi(III) substitution increases. No PL is observed from this family of semiconductors, but a crystal of Rb(23)Bi(III)(7)Sb(V)(2)Cl(54) exhibits a high resistivity of 1.0 × 10(10) Ω·cm and X-ray photoconductivity with a promising μτ product of 8.0 × 10(–5) cm(2) s(–1) V(–1). The unique 0D layered structures of the Rb(23)Bi(III)(x)Sb(III)(7–x)Sb(V)(2)Cl(54) family highlight the versatility of the ns(2) lone pair in semiconducting metal-halides, pointing the way toward new functional 0D metal-halide compounds.